A roadmap for advancing plant phenological studies through effective open research data management - Barbara Templ (Ecological Informatics)
Phenological research, critical for understanding ecological dynamics in response to environmental changes, increasingly relies on Open Research Data Management (ORDM) to enhance scientific outcomes. Based on insights from a structured survey conducted among phenology experts, this paper explores how the adoption of FAIR principles - Findability, Accessibility, Interoperability, and Reusability - directly addresses the unique challenges of phenological data, such as inconsistent metadata, variability in data collection methods, and difficulties in data integration. This synthesis not only highlights the obstacles faced by phenologists but also proposes strategic solutions highlighting a clear call to action steering phenological research toward a more collaborative and open science future.